THE PARTICULARITY OF THE CONFLICT OF LAWS IN MOROCCO: THE INVERSED CASE OF THE PERSONAL STATUTE OF FOREIGNERS. - Sayf Eddine Essadik (Indonesia Private Law Review, 2022)
Morocco has one of the oldest international private law statutes that are still working, to some extent. The environment in which that law was adopted and the current environment in Morocco are in complete and utter discord. Yet somehow, this statute stayed in effect and even today is applicable in competition with other laws. This paper strives to elucidate the complexity jurists in Morocco must deal with due to the absurdity in matters of the personal statute of foreigners. This paper seeks to explain the historical and legal basis for Morocco's approach to international private law, particularly in matters concerning the personal statute of foreigners. Not only has the general theory (qualification, public order, renvoi, and evasion of law) evolved in a specific way, but so has the application of these principles to the subject matter, the personal statute. Given the importance of the historic element in the adoption and development of this field, the method used for this study is juridical normative with historical-descriptive characteristics; a historical description is required. The research method used is qualitative. The findings of this paper will highlight the need for change or clarification of the confusion that this blending of different legal provisions causes for legal professionals and partitioners alike.